1999
DOI: 10.1016/s1388-1981(99)00010-4
|View full text |Cite
|
Sign up to set email alerts
|

Low C18 to C20 fatty acid elongase activity and limited conversion of stearidonic acid, 18:4(n–3), to eicosapentaenoic acid, 20:5(n–3), in a cell line from the turbot, Scophthalmus maximus

Abstract: The TF cell line, derived from a carnivorous marine teleost, the turbot (Scophthalmus maximus), is known to have a reduced rate of polyunsaturated fatty acid (PUFA) biosynthesis.In order to establish the enzymic step responsible, the metabolic conversions of a range of PUFA including the key intermediates of n-3PUFA metabolism, stearidonic acid (18:4n-3) and its elongation product 20:4n-3, were studied in TF cells and compared with the AS cell line derived from Atlantic salmon (Salmo salar). Cells were cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(35 citation statements)
references
References 43 publications
0
35
0
Order By: Relevance
“…Correspondingly, fishes fed vegetable oil (50% or 100%) had high levels of C18:3n-3 and C18:2n-6 but low levels of n-3 LC-PUFAs in their muscles and liver, and this was especially pronounced in the large yellow croaker. Previous studies have demonstrated that marine fish species show less ability to synthesize LC-PUFAs from C18:3n-3 and C18:2n-68922383940. However, the mechanisms involved in the dietary regulation of LC-PUFA synthesis have rarely been studied in fish to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correspondingly, fishes fed vegetable oil (50% or 100%) had high levels of C18:3n-3 and C18:2n-6 but low levels of n-3 LC-PUFAs in their muscles and liver, and this was especially pronounced in the large yellow croaker. Previous studies have demonstrated that marine fish species show less ability to synthesize LC-PUFAs from C18:3n-3 and C18:2n-68922383940. However, the mechanisms involved in the dietary regulation of LC-PUFA synthesis have rarely been studied in fish to date.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with freshwater fish, marine fish species generally lack the ability to synthesize LC-PUFAs from their 18-carbon precursor fatty acids89. However, euryhaline fish commonly show varying levels of capacity to synthesize LC-PUFAs, depending on the ambient salinity101112.…”
mentioning
confidence: 99%
“…Atlantic salmon have duplicated genes for both desaturases and elongases of fatty acids and, in the case of desaturases, duplicates appear to have diverged and neo- or subfunctionalised to provide enzymatic activities for the entire LC-PUFA pathway [26,27]. In contrast, other fish species, particularly marine carnivorous species, are incapable of endogenous production of significant amounts of LC-PUFA because they lack critical genes of the biosynthetic pathway [17,25,35]. It has been suggested that this enhancement of LC-PUFA capacity in salmonids has been a factor in their success in colonising relatively nutrient poor freshwater environments [27].…”
Section: Discussionmentioning
confidence: 99%
“…Certainly the discovery of a bifunctional enzyme in zebrafish is consistent with findings in the piscivorous marine species turbot (Scophthalmus maximus). In turbot, a deficiency in the fatty acid desaturation͞elongation pathway has been ascribed to a lack of C 18 -20 elongase function, while both ⌬6 and ⌬5 desaturase capabilities have been retained (40). However, in another marine species, gilthead sea bream (Sparus aurata), a block in the fatty acid desaturation͞elongation pathway has been identified as a deficiency in ⌬5 desaturase activity (41).…”
Section: Discussionmentioning
confidence: 99%